2019
DOI: 10.3390/plants8110463
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Alternaria Leaf Spot Caused by Alternaria spp. in Jerusalem Artichoke (Helianthus tuberosus L.) under Two Fertilization Regimes

Abstract: The objectives of this study were to evaluate the efficacy of integrating resistant genotypes of Jerusalem artichoke with Trichoderma harzianum isolate T9 to control Alternaria leaf spot caused by Alternaria spp. under two fertilization regimes and to determine whether T9 application induced chitinase and β-1,3-glucanase activity in Jerusalem artichoke leaves. Six Jerusalem artichoke varieties (resistant varieties JA15, JA86, and JA116 and susceptible varieties HEL246, HEL293, and JA109) and three disease cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Jerusalem artichoke ( H. tuberosus L.) is a hardy perennial crop in the family Asteraceae, with high adaptability to barren lands, such as salinized land and soil with high sediment, and is suitable for growing in dry, cold, and sunny climates [ 7 , 8 ]. Jerusalem artichokes are an important cash crop and can be used as human food [ 9 ], animal feedstock [ 10 , 11 ], and raw materials in the production of pharmaceuticals, cosmetics, biofuels [ 12 ], and ecological restoration [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jerusalem artichoke ( H. tuberosus L.) is a hardy perennial crop in the family Asteraceae, with high adaptability to barren lands, such as salinized land and soil with high sediment, and is suitable for growing in dry, cold, and sunny climates [ 7 , 8 ]. Jerusalem artichokes are an important cash crop and can be used as human food [ 9 ], animal feedstock [ 10 , 11 ], and raw materials in the production of pharmaceuticals, cosmetics, biofuels [ 12 ], and ecological restoration [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternaria disease is traditionally managed by applying chemical fungicides through spray treatments. Few studies reported success in controlling the disease in various crops, including Solanum tuberosum, Capsicum annuum, sunflower, and Jerusalem artichoke (Viriyasuthee et al, 2019). However, due to evolving agricultural policies, aiming to reduce pesticide use by up to 50% by 2030 and the adverse effects of such fungicides, there is a need for innovative strategies.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…However, due to evolving agricultural policies, aiming to reduce pesticide use by up to 50% by 2030 and the adverse effects of such fungicides, there is a need for innovative strategies. The use of resistant genotypes and biocontrol methods involving Trichoderma sp., however, have proven effective in peanuts, sunflower, chili, and aloe vera (Viriyasuthee et al, 2019) but not widely studied.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…can produce bioactive substances and have antagonistic effects on plant-pathogenic fungi and plant-pathogenic nematodes ( Şesan et al, 2020 ; Abdelkhalek et al, 2022 ; Organo et al, 2022 ; Rao et al, 2022 ). Bioactive substances, including secondary metabolites and cell wall-degrading enzymes, can effectively improve the resistance of crops, reduce plant diseases, and promote plant growth ( Domínguez et al, 2016 ; Viriyasuthee et al, 2019 ; Jaiswal et al, 2020 ; Tseng et al, 2020 ).…”
Section: Application and Mechanism Of Action Of Trichoderma...mentioning
confidence: 99%